Four new norlignan glycoside isomers from the twigs of Cephalotaxus oliveri Mast. Issue 12 (15th December 2017) - Meng, Fan-Cheng; Liu, Hui; Huang, Xiao-Jun; Chang, Yu; Ren, Dai; Lin, Li-Gen; Zeng, Qing-Qian; Zhang, Qing-Wen
Graphical abstract: Abstract: Four novel isomers of norlignan glycoside were isolated from Cephalotaxus oliveri Mast.. Their structures were elucidated as 3 S -4″- O - β -d -glucopyranosylnyasol1, 3 S -4′- O - β -d -glucopyranosylnyasol2, 3 S -4″- O - β -d -glucopyranosylhinokiresinol3, 3 S -4′- O - β -d -glucopyranosylhinokiresinol4 by extensive spectroscopic methods including 1D and 2D NMR experiments ( 1 H, 13 C, DEPT, 1 H– 1 H COSY, HSQC, HMBC, ROESY) along with HR-ESIMS and comparison to literature data. Their absolute configurations were elucidated through CD spectra coupled with the quantum chemical CD calculations. Abstract : (3 S )-4″- O - β -d -Glucopyranosylnyasol: C23 H26 O7 [ α ]D 20 = +119.0 ( c 0.03, MeOH) Source of chirality: natural product from Cephalotaxus oliveri Absolute configuration: (3 S, 1‴ S, 2‴ R, 3‴ S, 4‴ S, 5‴ R ) Abstract : (3 S )-4′- O - β -d -Glucopyranosylnyasol: C23 H26 O7 [ α ]D 20 = +95.0 ( c 0.1, MeOH) Source of chirality: natural product from Cephalotaxus oliveri Absolute configuration: (3 S, 1‴ S, 2‴ R, 3‴ S, 4‴ S, 5‴ R ) Abstract : (3 S )-4″- O - β -d -Glucopyranosylhinokiresinol: C23 H26 O7 [ α ]D 20 = −16.6 ( c 0.05, MeOH) Source of chirality: natural product from Cephalotaxus oliveri Absolute configuration: (3 S, 1‴ S, 2‴ R, 3‴ S, 4‴ S, 5‴ R ) Abstract : (3 S )-4′- O - β -d -Glucopyranosylhinokiresinol: C23 H26 O7 [ α ]D 20 = –38.3 ( c 0.13, MeOH) Source of chirality: natural product from Cephalotaxus oliveri Absolute configuration: (3 S, 1‴ S, 2‴ R, 3‴ S, 4‴ S, 5‴ R )